HIGHER EDUCATION MARKETING CONCERNS: THE FACTORS INFLUENCING STUDENTS’ CHOICE FOR PRIVATE UNIVERSITY - Erlita Ridanasti (Jurnal Riset Manajemen dan Bisnis, 2017)
ABSTRACT This research aims to find the most important factors that affects students’ decision making in choosing university. The research subject of this study uses quantitative survey for exploratory research. The sample of this study is 90 students of the twelfth grade of top level senior high school. For major choice, the result shows career opportunity as the most important factor. Students choose career opportunity because of their expectation to the major in providing promising job for them after graduation. For university choice, descriptive data shows prominence as the most important factor influencing students’ decision to choose university. The reputable tutor is considered as the criteria to represent that university is a reputable one. In addition, this finding would bring evaluation for the private university to provide reputable tutor in order to improve the university prominence. Further, the result of this research will concern more to university strategy for students’ recruitment. Keywords: higher education, university choice, major choice ABSTRAK Penelitian ini bertujuan untuk mengetahui faktor yang paling mempengaruhi keputusan siswa dalam menentukan pilihan universitas. Subjek penelitian dari studi ini menggunakan survey kuantitatif untuk penelitian exploratori. Sample dari penelitian ini menggunakan 90 siswa pada tingkat dua belas di tiga sekolah menengah atas negeri di Yogyakarta. Dalam memilih jurusan, hasil menunjukan bahwa peluang karir merupakan faktor paling penting dalam mempengaruhi keputusan siswa. Siswa memilih peluang karir sebagai faktor paling penting karena mereka berharap bahwa jurusan yang mereka pilih mampu menyediakan pekerjaan yang menjanjikan setelah lulus. Sedangkan, dalam memilih universitas data deskriptif menunjukkan bahwa reputasi universitas menjadi faktor paling penting bagi siswa dalam pengambilan keputusan menentukan universitas. Pengajar yang memiliki reputasi menjadi kriteria yang paling dipertimbangkan untuk menunjukkan bahwa universitas memiliki reputasi. Penemuan ini memberikan evaluasi bagi universitas swasta untuk menyediakan pengajar yang bereputasi dalam rangka meningkatkan reputasi universitas. Hasil dari penelitian ini, selanjutnya akan lebih difokuskan pada strategi rekrutmen di universitas. Kata kunci: pendidikan tinggi, pilihan universitas, pilihan jurusan